2011
DOI: 10.5194/nhess-11-2391-2011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the 2010 Chilean tsunami using satellite altimetry

Abstract: Abstract. Tsunamis are difficult to detect and measure in the open ocean because the wave amplitude is much smaller than it is closer to shore. An effective early warning system, however, must be able to observe an impending tsunami threat far away from the shore in order to provide the necessary lead-time for coastal inhabitants to find safety. Given the expansiveness of the ocean, sensors capable of detecting the tsunami must also have very broad areal coverage. The 2004 Sumatra-Andaman tsunami was definitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…To extract the tsunami signal from the background ocean variability in the SSH measurements, the filtering technique introduced in Hamlington et al [2011] is implemented. This filtering technique is based on the method developed by Gower [2007]consisting of subtracting a smoothed average (9‐second boxcar filter) of SSH measured on the same pass of the cycles before and after the tsunami cycle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To extract the tsunami signal from the background ocean variability in the SSH measurements, the filtering technique introduced in Hamlington et al [2011] is implemented. This filtering technique is based on the method developed by Gower [2007]consisting of subtracting a smoothed average (9‐second boxcar filter) of SSH measured on the same pass of the cycles before and after the tsunami cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, recent studies have demonstrated the ability to detect a tsunami in the open ocean through changes in the sea surface characterized by the radar backscattering strength at nadir, σ 0 [ Godin et al , 2009; Hamlington et al , 2011]. To determine if σ 0 variations were induced by the 2011 Tohoku tsunami, we perform statistical randomization tests to compare data with and without the tsunami present.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of other offshore measurements, satellite altimetry has been well known to detect significant tsunamis (Gower 2004;Hamlington et al 2011;Song et al 2012), and its nearreal-time use has been also investigated (Hamlington et al 2012). GNSS-reflectometry using numerous GNSS satellites and LEO satellites may also be a promising technique for detecting offshore tsunamis over vast areas of ocean in a relatively short time interval (Stosius et al 2010).…”
Section: Summary and Remarksmentioning
confidence: 99%